2022
DOI: 10.32479/ijeep.12941
|View full text |Cite
|
Sign up to set email alerts
|

Europe in World Natural Gas Market: International Transmission of European Price Shocks

Abstract: The paper applies the Vector Error Correction Model (VECM) framework with 250 days rolling window to the analysis of the interconnectedness of regional markets for natural gas in Europe, the Asia-Pacific region and the US. Transmission of European gas market fundamentals to other regional gas markets is assessed by using carbon price in the EU Emissions Trading System and European gas storage capacity utilization. The latter is proven to be a significant component in the cointegrating equation that links natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…7 . The correlation between the two pricing systems was also observed in an analysis of daily prices presented by Kpytin et al [ 130 ]. It was further revealed that daily JKM-TTF correlation was impacted during COVID-19 pandemic where the two markets diverged
Fig.
…”
Section: Resultssupporting
confidence: 53%
“…7 . The correlation between the two pricing systems was also observed in an analysis of daily prices presented by Kpytin et al [ 130 ]. It was further revealed that daily JKM-TTF correlation was impacted during COVID-19 pandemic where the two markets diverged
Fig.
…”
Section: Resultssupporting
confidence: 53%